2021
DOI: 10.1186/s12910-021-00617-3
|View full text |Cite
|
Sign up to set email alerts
|

Unapproved clinical trials in Russia: exception or norm?

Abstract: Background In modern Russia, any clinical investigation of a pharmaceutical for use in humans is subject to prior evaluation and approval by the Ministry of Health and its Central Ethics Committee. Despite this, some researchers and trial sponsors fail to comply, this is particularly true in case of the studies initiated by domestic sponsors or sponsor-investigators and published in Russian language medical journals. This exploratory research aims to discover whether it is a sporadic non-compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Even by the nation's own standards, there are reasons to believe that Russia's record of compliance has been poor. Clinical pharmaceutical studies in Russia are supposed to be governed by the Central Ethics Committee of the Ministry of Health and regulated by the federal Law of April 12, 2010, FZ‐61, “On the Circulation of Medicinal Products” 7 and the Ministry of Health's Order 200n, “On Approval of Rules for Good Clinical Practice.” 8 According to these regulations, human subjects recruitment must be “aimed at … [r]especting the rights of participants,” protecting their health, and verifying “the scientific validity of the study based on non‐clinical tests and previous clinical investigations.” 9 …”
Section: Clinical Trials In Russiamentioning
confidence: 99%
See 1 more Smart Citation
“…Even by the nation's own standards, there are reasons to believe that Russia's record of compliance has been poor. Clinical pharmaceutical studies in Russia are supposed to be governed by the Central Ethics Committee of the Ministry of Health and regulated by the federal Law of April 12, 2010, FZ‐61, “On the Circulation of Medicinal Products” 7 and the Ministry of Health's Order 200n, “On Approval of Rules for Good Clinical Practice.” 8 According to these regulations, human subjects recruitment must be “aimed at … [r]especting the rights of participants,” protecting their health, and verifying “the scientific validity of the study based on non‐clinical tests and previous clinical investigations.” 9 …”
Section: Clinical Trials In Russiamentioning
confidence: 99%
“…9 However, an investigation carried out in 2021 by members of the Russian Academy of Sciences Commission for Counteracting the Falsification of Scientific Research found that 22 out of 26 clinical trials had done one or more of the following: published articles that did not comply with the established mandatory rules for clinical trials authorization, conducted studies in which the investigators manifested methodologies that did not correlate with related publications, or reported that the "investigational product was efficacious, despite there being no statistically significant difference between the compared treatment arms. " 10 The Russian Academy of Sciences commission concluded that "[p]ublications of clinical study results in Russian journals frequently do not meet common standards and contain large evidence of ethical, scientific, and publishing breaches. " 11 These concerns were deepened during the research that the Russian Direct Investment Fund, the Kremlin's sovereign wealth fund, sponsored for the development of the Covid-19 Sputnik V vaccine.…”
Section: Clinical Trials In Russiamentioning
confidence: 99%
“…Since we employed a retrospective analysis as a method, and, therefore, analysed already collected data, then, there is no any necessity to obtain any Review Board Statement, according to both Swiss [ 52 ] and Russian [ 53 ] regulations.…”
mentioning
confidence: 99%
“…Since we worked only with the already collected data (we applied a retrospective analysis as a method) and all patients undersighned their consent for the treatment in Clinic, therefore, this retrospective study is exempt from the necessity to provide any Informed Consent Statement according to both Swiss [ 52 ] and Russian [ 53 ] regulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation